2008
DOI: 10.1111/j.1574-0862.2008.00339.x
|View full text |Cite
|
Sign up to set email alerts
|

An analysis of the impact of swine CAFOs on the value of nearby houses

Abstract: The impact of 39 swine confined or concentrated animal feeding operations (CAFOs) in Black Hawk County, Iowa on 5,822 house sales is explored by introducing a new variable that more accurately captures the effects of prevailing winds, exploring potential adverse effects within concentric circles around each CAFO, managing selection bias, and incorporating spatial correlation into the error term of the empirical model. Large adverse impacts suffered by houses that are within 3 miles and directly downwind from a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 8 publications
2
16
0
Order By: Relevance
“…The statistical model for lake visitation is then applied alongside models from the literature (Sneeringer, 2009;Isakson & Ecker, 2008) for the relationship between hog production emissions and infant mortality and the relationship between hog production emissions and residential home values to estimate the potential benefits of reducing hog production emissions in Iowa counties. The county-level birth rate data used to run the infant mortality model was obtained from the Iowa Department of Education.…”
Section: Estimates Of Median [1st and 3rd Quartile] Increase In Lake mentioning
confidence: 99%
See 3 more Smart Citations
“…The statistical model for lake visitation is then applied alongside models from the literature (Sneeringer, 2009;Isakson & Ecker, 2008) for the relationship between hog production emissions and infant mortality and the relationship between hog production emissions and residential home values to estimate the potential benefits of reducing hog production emissions in Iowa counties. The county-level birth rate data used to run the infant mortality model was obtained from the Iowa Department of Education.…”
Section: Estimates Of Median [1st and 3rd Quartile] Increase In Lake mentioning
confidence: 99%
“…This chapter estimates property value damage using the value of owner-occupied residential homes near AFOs, not including nonresidential buildings or rental units, with a hedonic model developed by Isakson & Ecker (2008) based on Black Hawk County, Iowa which relates the hog production rate at AFOs to nearby home values.…”
Section: Types Of Pollution Damagementioning
confidence: 99%
See 2 more Smart Citations
“…Odors may also lead to health problems (Dalton et al, 2011). Odors from livestock facilities are so significant that they negatively affect home values (Palmquist et al, 1997;Isakson & Ecker, 2008). A study from Iowa found that there may be a 9% drop in property value if a moderately-sized livestock operation is located upwind and near a residence (Herriges et al, 2005).…”
Section: State Laws and Local Ordinancesmentioning
confidence: 99%